Analasis Pendapatan Peternak Sapi Potong di Kecamatan Malaka Timur Kabupaten Malaka: Income Analysis of Beef Cattle Farmers in East Malaka District, Malaka Regency - Asa, Yoseph; Lole, Ulrikus R.; Makandolu, Solvi M.; Sol'uf, Morin M. (Jurnal Peternakan Lahan Kering, 2024)
A study on Income Analysis of Beef Cattle Farmers in East Malacca District has been conducted with the aimof analyzing income and factors affecting the business. Factors were identified such as feed costs, healthcosts, cage and equipment costs, length of maintenance, as well as the number of livestock sold. The researchmethod used is a survey method with data collection techniques, namely observation, interviews, anddocumentation to obtain primary data and secondary data. Sampling is carried out through two stages,namely the purposive stage of determining sample villages and the stage of determining respondentsrandomly disproportionately. The analysis method used is income analysis to see the income earned byfarmers and multiple linear regression analysis with Cobb-Douglas climbing to assess the factors identifiedas affecting or not on income. The results showed that the average income obtained by farmers from beefcattle farming was Rp23,049,219.05/year. Furthermore, the results of multiple linear regression analysisshowed that income was closely related to the length of livestock rearing (X4) and the number of livestocksold (X5) Suatu penelitian tentang analisis pendapatan peternak sapi potong di Kecamatan Malaka Timur telahdilakukan dengan tujuan untuk menganalisis pendapatan dan faktor-faktor yang mempengaruhi usahatersebut. Faktor-faktor yang diidentifikasi terdiri dari biaya pakan, biaya kesehatan, biaya kandang danperalatan, lama pemeliharaan, serta jumlah ternak yang dijual. Metode penelitian yang digunakan adalahmetode survei dengan teknik pengumpulan data yaitu observasi, wawancara, dan dokumentasi untukmemperoleh data primer serta data sekunder. Pengambilan contoh dilakukan melalui dua tahap yaitu tahappenentuan desa contoh secara purposive dan tahap penentuan responden secara acak non proporsional.Metode analisis yang digunakan adalah analisis pendapatan untuk melihat pendapatan yang diperolehpeternak dan analisis regresi linear berganda dengan pendakatan Cobb-Douglas untuk mengetahui faktor-faktor yang diidentifikasi berpengaruh atau tidak terhadap pendapatan. Hasil penelitian menunjukkan bahwarata-rata pendapatan yang diperoleh petenak dari usaha ternak sapi potong adalah Rp23.049.219,05/tahun.Selanjutnya hasil analisis regresi linear berganda menunjukkan bahwa pendapatan berhubungan erat denganlama pemeliharaan ternak (X4) dan jumlah ternak yang dijual (X5)